Heidelberg Retina Tomography II parameters in evaluating high- and normal-pressure glaucoma progression - Risović, Dušica; Gvozdenović, Ranko; Marjanović, Ivan; Abazi, Zihret; Stamenković, Miroslav (Vojnosanitetski pregled, 2014)
Background/Aim. Heidelberg retina tomography II (HRT II) haves been employed to quantitatively assess the topography of optic discs in eyes with high-pressure glaucoma (HPG) and normal-pressure glaucoma (NPG), in order to determine which of global and segmental optic disc parameters will prove to be most suitable for monitoring the progression of these two conditions. Methods. The results of 73 eyes of 73 patients with HPG and NPG were analyzed in relation to age, refractive error, quality of HRT images and stereometric parameters. Results. A statistically significant difference (p < 0.05) between the global baseline and follow-up results was found in: rim volume, maximum cup depth and cup shape measure (in the HPG group), and C/D ratio, cup volume, rim volume and cup shape measure (in the NPG group). The baseline and follow-up results of the retinal nerve fiber layer in the temporal and inferotemporal sectors show a significant difference in both groups. Conclusion. Several HRT stereometric parameters are useful for monitoring the progression of changes of the optic disc and local retina in eyes with HPG and NPG. Both segmental and global scanning is of importance in glaucoma progression analysis.
Keywords: glaucoma; retina; tomography; disease progression